Effect of Preoperative Breathing Exercise on Postoperative Patients’ Lung Functions - Dhiaa A. Al-Reda1, Rajha A. H1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pulmonary complications after surgery are a major cause of morbidity and mortality and therefore are a source area of concern in both developed and developing countries. Presently, surgical patients didn’t acquire education about deep breathing activities that were adequate and many of them only received some education post operation. Aim of the study: To investigate the Effect of Preoperative Breathing Exercise on Postoperative patients’ Lung Functions. A quantitative quasi-Experimental, Pre-Test and Post-Test design. A non-probability (purposive sample) of (60) patients divided into two equal groups distributed as the case and control groups (30) patients for the case group are exposed to the breathing exercise program, Pursed-lip method, and (30) patients without exposed to the breathing exercise program categories as control group. the study have been carried out in Al-Diwaniyah teaching hospital, This study conducted from 22nd of October 2018 to 25th of June 2019. There were statistically significant difference between case and control groups, patients in the case group had improvement in all parameters of lung functions than control group ( P < .05) in the two periods of measurement post-operatively. The program show obvious difference between the lung function for both study and control groups during the post-test.